A bioactive poly(ether-ether-ketone) nanocomposite scaffold regulates osteoblast/osteoclast activity for the regeneration of osteoporotic bone. Issue 42 (14th October 2022) - Zhao, Mengen; Chen, Guo; Zhang, Shixiong; Chen, Bin; Wu, Zhaoying; Zhang, Chao
Abstract : The ASP composite scaffold promoted osteogenesis and inhibited osteoclastogenesis, which could serve as a bioactive material for bone regeneration of osteoporotic defects. Abstract : Due to the lower regeneration capacity of the osteoporotic bone, the treatment of osteoporotic defects is extremely challenging in clinics. In this study, strontium-doped bioactive glass nanoparticles loaded with sodium alendronate (ALN), namely A-SrBG, were incorporated into the poly(ether-ether-ketone) matrix to fabricate a bioactive composite scaffold (ASP), which was expected to both inhibit bone resorption and promote bone regeneration. The results showed that such a composite scaffold with interconnected macropores (200–400 μm) could release Ca 2+, Sr 2+, and ALN in vitro . The proliferation, alkaline phosphatase (ALP) activity, expression of osteogenesis-related genes, and formation of calcified nodules of rat bone marrow stromal cells (rBMSCs) were clearly evidenced, and the reduction in the proliferation, tartrate-resistant acid phosphatase (TRAP) activity, cell fusion, and expression of osteoclastogenesis-related genes of osteoclasts was observed as well. In the presence of the ASP scaffold, enhanced osteogenesis along with inhibiting osteoclastogenesis was observed by modulating the osteoprotegerin (OPG)/receptor activator for nuclear factor κB ligand (RANKL) ratio. The efficacy of the composite scaffold in the regeneration of osteoporotic critical-sized cranial defect in a rat model was evaluated. Therefore, the bioactive composite scaffold with excellent biocompatibility and osteogenic potential could be a promising material for the repair of osteoporotic bone defects.